2009
DOI: 10.1111/j.1365-2621.2007.01660.x
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of rancidity inhibition during frozen storage of Wels catfish (Silurus glanis) fillets by previous ascorbic and citric acid treatment

Abstract: The effect of preliminary ascorbic and citric acid (AA and CA, respectively) soaking treatments on the rancidity development in Wels catfish (Silurus glanis) fillets during further frozen storage ()18°C; up to 6 months) was studied. Rancidity development was measured by biochemical quality indices (formation of free fatty acids, peroxides and secondary oxidation products) and compared with sensory analysis (appearance, rancid odour and consistency) and general chemical analyses (pH, expressible moisture and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 37 publications
(41 reference statements)
4
36
0
3
Order By: Relevance
“…Thus, CA and its salts have shown to play a synergist role with primary antioxidants and oxygen scavengers during the refrigerated [10,34] and frozen [12,13] storage of marine species. In the same way, AA and its salts have been reported to act as antioxidants in fish oil [7], minced fish [9], fish fillets [11] and whole fish [13] because of their oxygen scavenger and reducing roles.…”
Section: Lipid Oxidation Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, CA and its salts have shown to play a synergist role with primary antioxidants and oxygen scavengers during the refrigerated [10,34] and frozen [12,13] storage of marine species. In the same way, AA and its salts have been reported to act as antioxidants in fish oil [7], minced fish [9], fish fillets [11] and whole fish [13] because of their oxygen scavenger and reducing roles.…”
Section: Lipid Oxidation Assessmentmentioning
confidence: 99%
“…Thus, ascorbic and citric acids (AA and CA, respectively) and their salts are widely known for their role as chelators, acidulants in biological systems and synergists of primary antioxidants, so that a profitable effect on fish oil and emulsions [7,8], minced fish [9,10], fish fillets [11,12] and whole fish [13] have been observed. Further, lactic acid (LA) has been reported to be effective in suppressing Gram-negative bacteria, which are known to be the most important fish spoiler group; thus, LA pre-treatment has shown to be effective in preserving and extending shelf-life in fish fillets [14,15] and coated fish [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, a preserving effect on such fatty acid parameters could be observed resulting from the previous AA treatment, which Effect of previous ascorbic acid treatment on the fatty acid profile of cobia (Rachycentron canadum) fillets during frozen storage permitted concentrations for its use (Madrid et al, 1994;Giese, 1996). Thus, AA is widely known for its role as chelator and acidulant in biological systems and as a synergist of primary antioxidants, so that a positive effect on shelf life increase has been described for marine oils (Hamilton et al, 1998), minced fish (Hwang and Regenstein, 1988), fish fillets (Kilinc et al, 2009;Pourashouri et al, 2009) and whole fish (Aubourg et al, 2004;Sanjuás et al, 2011). Cobia (Rachycentron canadum) fish is the only species in the family Rachycentridae.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, AA and other natural organic acids have been successfully employed in different kinds of fish species such as Wels catfish (Silurus glanis) (Pourashouri et al 2009) and horse mackerel (trachurus trachurus) (Aubourg et al, 2004). Similarly, different kinds of vegetable extracts have been employed as previous soaking treatments such as rosemary extract and onion juice for sardine (Sardina pilchardus) mince (Serdaroglu and Felekoglu, 2005) and a flaxseed extract has been used on whole mackerel (Scomber scombrus) (Stodolnik et al, 2005).…”
Section: Effect Of Aa Dippingmentioning
confidence: 99%
“…Thus, ascorbic and citric acids (AA and CA, respectively) are widely known for their role as chelators, acidulants in biological systems and synergists of primary antioxidants, so that a profitable effect on fish fillets (Badii and Howell, 2002;Kilinc et al, 2009;Pourashouri et al, 2009) and whole fish has been observed. Further, lactic acid (LA) has been reported EFFECT OF DIFFErENT ICING CONDITIONS ON LIPID DAMAGE DEVELOPMENT IN CHILLED HOrSE MACKErEL (TRAChuRuS… to be effective in suppressing Gram-negative bacteria, which are known to be the most important fish spoiler group; thus, LA pre-treatment has shown to be effective in preserving and extending shelf life in fish fillets (Kim et al, 1995;Metin et al, 2001;Erkan, 2003), coated fish (Gogus et al, 2006) and fish slices (Sallam, 2007).…”
Section: Introductionmentioning
confidence: 99%